PRODUKSI TELUR DAN PENDAPATAN PETERNAK ITIK PADA PEMELIHARAAN SECARA GEMBALA DAN TERKURUNG DI DAERAH PERTANIAN DAN PERIKANAN (DUCK EGG PRODUCTION AND FARMERSâ INCOME UNDER EXTENSIVE AND INTENSIVE SYSTEMS IN AGRICULTURAL AND FISHERY CENTERS) - , Ismoyowati; Suswoyo, Imam (Pembangunan Pedesaan, 2011)
The purpose of this research was to study the differences of egg production and income of duck farming in agriculural and fishery areas. Accordingly, the areas had different altitude natural resources to support the existing duck farming. Survey method was applied with respondents of extensive and intensive duck farmers in Purbalingga Regency as a center of agricultural area and Cilacap Regency as a center of fishery area. Data consisted of primary data as a result of direct observation and discussion with respondents. Parameters observed were egg production, farm size, costs of production, farm revenue and income. Data were analysed using variance analysed based on the nested classification and honestly significance different. The results showed that the intensive farming in the agricultural area (Purbalingga) had a higher egg production (60.42%) than that in the fishery area (Cilacap). Farm revenue and production cost under intensive system in agricultural area was higher; consequenlty the income of both sysems in the area relatively similar. It can be concluded that egg production was higher in the agricultural area, but the farm revenue under extensive and intensive systems in the both areas relatively similar.